INFLUENCE OF WATER AND PRECURSOR MOLARITY ON THE TiO2 THIN FILMS DEPOSITED FROM SOLVENTLESS SOL-GEL - Shuhadah, A.Y.; Rosli, Z. M.; Juoi, J. M.; Johari, N. D.; Suzaim, F. H.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Titania (TiO2) of anatase, anatase-rutile and anatase-brookite-rutile thin films were successfully established from sol-gel dip coating technique using titanium tetraisopropoxide (TTIP) as precursors without the presence of solvent. The thin films were deposited on glass substrate and the type of TiO2 crystalline structure produced was depending upon the molar ratio of the TTIP and water. Results shown that the TTIP molarity is more substantial in determining the TiO2 thin films crystallinity and crystallite size as compared to the water molarity. Meanwhile, the desired phases and crystallite size can be controlled by manipulating the molar ratio of water and TTIP. Thus, the establishment of the desired phases (anatase mixed rutile), crystallinity and crystallite size (anatase: 15 nm, rutile: 30 nm) of TiO2 thin films from solvent less sol-gel can be controlled and encouraging to explore as an effort toward producing a sustainable green photocatalytic material.